-x - y = 8
2x - y = -1
Ok, we are going to solve this in 2 parts. First we have to solve for one of the variables in one of the equation in terms of the other variable. I like to take the easiest equation first and try to avoid fractions, so let's use the first equation and solve for x.
-x - y = 8 add y to each side
-x = 8 + y divide by -1
x = -8 - y
So now we have a value for x in terms of y that we can use to substitute into the other equation. In the other equation we are going to put -8 - y in place of the x.
2x - y = -1
2(-8 - y) - y = -1 multiply the 2 through the parentheses
-16 - 2y - y = -1 combine like terms
-16 - 3y = -1 add 16 to both sides
-3y = 15 divide each side by -3
y = -5
Now we have a value for y. We need to plug it into either of the original equations then solve for x. I usually choose the most simple equation.
-x - y = 8
-x - (-5) = 8 multiply -1 through the parentheses
-x + 5 = 8 subtract 5 from each side
-x = 3 divide each side by -1
x = -3
So our solution set is
(-3, -5)
That is the point on the grid where the 2 equations are equal, so that is the place where they intersect.
Answer:
-4.3
Step-by-step explanation:
5.4 +(-9.7)
= 5.4-9.7
=-4.3
Answer:
i believe its 12.55
Step-by-step explanation:
if you add both number, 12.90 and 12.20, then divide by 2.
you'll will gain the same result
Answer:
i would have to say the square root of 26 since its 5.099
Step-by-step explanation:
Circumference = πD
πD = 56.52
D = 17.99 in
Area of the pizza = π (17.99 ÷ 2)² = 254.19 in²
Area of the pizza eaten = 254.19 ÷ 4 = 63.55 in²
Area of the pizza remain = 254.19 - 63.55 = 190.64 in²
Answer: 190.64 in²